2009
DOI: 10.1590/s1678-77572009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental conditions on properties of ionomeric and resin sealant materials

Abstract: Objectives:The aim of this study was to determine the effect of environmental conditions on the degradation of ionomeric and resin sealant materials.Material and Methods:FluroShield, Vitremer, and Ketac Molar disc-shaped specimens (n=18/material) were prepared, polished, subjected to initial hardness and roughness readings. Six discs of each material were randomly assigned to one of three different storage solutions: 0.3% citric acid (CA), demineralization solution (DE), and remineralization solution (RE). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
3
12
0
2
Order By: Relevance
“…The fluoride release of a fluoride-containing dental material may also be influenced by external variables such as the pH (Kosior and Kaczmarek 2006;Shen et al 2007;Kantovitz et al 2009) and the type of storage media used (Bell et al 1999;Hayacibara et al 2004;Kosior and Kaczmarek 2006). Kosior and Kaczmarek (2006), who investigated the fluoride release from a dental FS after immersion into three different storage media (de-ionized water, saline and artificial saliva) and at different pH (4.5-7.5), concluded that the highest cumulative fluoride release was detected in saline and the lowest in artificial saliva and at neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…The fluoride release of a fluoride-containing dental material may also be influenced by external variables such as the pH (Kosior and Kaczmarek 2006;Shen et al 2007;Kantovitz et al 2009) and the type of storage media used (Bell et al 1999;Hayacibara et al 2004;Kosior and Kaczmarek 2006). Kosior and Kaczmarek (2006), who investigated the fluoride release from a dental FS after immersion into three different storage media (de-ionized water, saline and artificial saliva) and at different pH (4.5-7.5), concluded that the highest cumulative fluoride release was detected in saline and the lowest in artificial saliva and at neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…However, under acidic conditions, there is greater likelihood of the fluoride being complexed and not available as free Fions. The reduced pH, with extra H + ions available, may lead to the formation of un-dissociated HF, and the increased release of Al 3+ leads to the possibility of the occurrence of such complexed species as AlF 2+ , AlF 2 +70 or even AlF 4 - 71 . Experimental results with a fluoride ion selective electrode have suggested that under acidic conditions almost all of the fluoride is complexed in some way 22 .…”
Section: Fluoride Release Patternsmentioning
confidence: 99%
“…With the advent of modern dentistry, preservation of the dental structure and avoidance of surgical treatment have become treatment goals (1,2). In this sense, pit-and-fissure sealants have been recognized as an effective method for preventing caries initiation and arresting caries progression by providing a physical barrier that inhibits microorganisms and food particles from collecting in pits and fissures (3).…”
Section: Introductionmentioning
confidence: 99%